An exploratory study of Rhodes students' attitudes and perceptions towards HIV/Aids - Weston, Robyn (Rhodes University, Faculty of Humanities, Department of Psychology, 2008)
The present study explores Rhodes students' perceptions and attitudes towards HIV/Aids issues. This study focuses on risk behaviour, stigmatisation, social perceptions and voluntary counselling and HIV testing (VCT). There is a lack of research on student attitudes, knowledge and behaviour at Rhodes University. It was therefore deemed pertinent to research this topic in that context. It was envisaged that the study would provide insights to be used in the formulation of improved strategies for HIV/Aids programs and education, ultimately impacting on the exponential increase of the pandemic in the Southern African region. A sample of six hundred and seventy five Rhodes University undergraduates completed a survey and its findings were interpreted in terms of relevant literature. A mixed methods approach using qualitative and quantitative methods was used. A focus group consisting of seven post-graduate students informed the development of the survey along with relevant literature. Four departments from the faculties of Commerce, Humanities, Science and Law were randomly sampled for the survey phase. Statistica was used to calculate descriptive statistics while the chi-square statistic was applied to examine the relationships between the variables. The findings show that the majority of students have high intention levels in planning to use preventative behaviour. However, in practise, this may not be the case. Many students feel that they belong to high or medium risk groups, as opposed to the low-risk groups. In terms of motivation levels, only sixty three percent of students are highly motivated to protect themselves from HIV/Aids and one third of respondents felt that they could not ask their partner to accompany them for an HIV/Aids test. In addition, students who had received VCT were more likely to be positive about the counselling process.
Keywords: Rhodes University -- Students; Rhodes University -- Students -- Attitudes; Counseling in higher education; AIDS (Disease) -- Prevention -- South Africa; HIV infections -- South Africa; AIDS (Disease) -- Study and teaching -- South Africa; HIV infections -- Study and teaching -- South Africa; HIV infections -- Diagnosis -- South Africa